Responsivitas Dinas Lingkungan Hidup Dalam Pelayanan Persampahan Di Kota Magelang - Eny Boedi Orbawati; Retno Dewi Pramodia Ahsani (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2019)
The significant growth of urban population gives impact to the increasing waste production. One of main concern of Local Government of Magelang is the waste management. Waste volume in Magelang increasing significantly become 160,58 M (2015) with 136,75 M transported waste which equal to .85,16% and 96% of population have been served by waste management network. This paper uses descriptive approach. Main focus of research is Responsiveness of Environment Unit on Waste Management in Magelang. Research’s result explain that Environment Unit waste management responsiveness manifest at (1) Potential responsiveness, involving community to create waste management policy, (2) actual responsiveness, fulfilment of community interest in waste management, (3) Resources Commitment responsiveness in waste management by integrated institution aspect, technical, and funding.